2017
DOI: 10.1016/s1470-2045(17)30251-6
|View full text |Cite
|
Sign up to set email alerts
|

Treatment of metastatic uveal melanoma with adoptive transfer of tumour-infiltrating lymphocytes: a single-centre, two-stage, single-arm, phase 2 study

Abstract: Background Uveal melanoma is a rare tumor with no established treatments once metastases develop. Although a variety of immune based therapies have demonstrated efficacy in metastatic cutaneous melanoma, their use in ocular variants has been disappointing. Recently, adoptive T cell therapy has shown salvage responses in multiple refractory solid tumors. Thus, we sought to determine if adoptive transfer of autologous tumor infiltrating lymphocytes (TIL) could mediate regression of metastatic uveal melanoma. M… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
193
0
3

Year Published

2017
2017
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 238 publications
(197 citation statements)
references
References 35 publications
1
193
0
3
Order By: Relevance
“…However, a lack of PD-L1 expression does not mean that uveal melanoma is 'immunotherapy resistant'. Indeed, immunotherapeutic interventions like adoptive T-cell transfer seems promising for control of metastatic disease in uveal melanoma [43]. Our study is limited by the number of samples assessed for PD-1 expression on TILs as well as the lack of characterization of TILs to identify specific lymphocyte subsets.…”
Section: Discussionmentioning
confidence: 99%
“…However, a lack of PD-L1 expression does not mean that uveal melanoma is 'immunotherapy resistant'. Indeed, immunotherapeutic interventions like adoptive T-cell transfer seems promising for control of metastatic disease in uveal melanoma [43]. Our study is limited by the number of samples assessed for PD-1 expression on TILs as well as the lack of characterization of TILs to identify specific lymphocyte subsets.…”
Section: Discussionmentioning
confidence: 99%
“…No significant difference was seen among responders and non-responders in terms of mutation burden in tumors. On the other hand, TIL products with either less than 3% tumorreactive T cells, less than 2 × 10 9 tumor-reactive T cells, or less than 100 pg/mL of tumor-induced IFN-γ release yielded poor clinical responses [65] . This study indicated that adoptive transfer of autologous TILs can mediate objective tumor regression in patients with metastatic UM.…”
Section: Adoptive Immunotherapy Using Tumor-infiltrating T Cellsmentioning
confidence: 98%
“…In a study at National Cancer Institute (NCT01814046), 21 metastatic UM patients who were HLA-A2 positive were treated with TIL therapy in phase II clinical trial [65,66] . Seven of 20 evaluable patients showed objective tumor regression including 6 patients with PR and one patient with CR, ongoing at 21 months post therapy.…”
Section: Adoptive Immunotherapy Using Tumor-infiltrating T Cellsmentioning
confidence: 99%
“…This is particularly true for patients with modestly mutated cancers arising from epithelial organs, collectively the leading causes of adult cancer‐related deaths . Detailed immune monitoring studies of exceptional patient responders to immunotherapy have revealed three critical variables that simultaneously must be satisfied for cancer regression to occur . First, the patient must possess a repertoire of T cells capable of recognizing antigens displayed on the surface of cancer cells.…”
Section: Introductionmentioning
confidence: 99%